RELIGIOUS ARCHETYPES IN MY NAME IS KHAN MOVIE - Chitra, Bima Prana; Erwina, Emmy; Nurtartila, Nurtartila (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to explore the representation and function of religious archetypes in the movie My Name Is Khan, directed by Karan Johar and written by Shibani Bathija. Employing Carl Gustav Jung’s archetype theory and Claude Lévi-Strauss’ structuralism as analytical frameworks, this research identifies the recurring religious archetypes that shape the characters and moral structures within the film. The qualitative method was used, focusing on textual and contextual analysis of dialogues and scenes from the movie that reflect archetypal elements. The findings reveal six dominant archetypes—The Great Mother, The Wise Old Man, The Hero, The Angel, The Caregiver, and Sufism. Each archetype serves to strengthen the film’s moral and spiritual message about humanity, compassion, and religious tolerance. The film not only reflects universal archetypal values but also offers a humanistic portrayal of faith amid discrimination. Ultimately, this research demonstrates that My Name Is Khan transcends religious narratives by portraying spiritual resilience, empathy, and universal values of goodness. Keywords: Religious archetypes, structuralism, Jungian theory, spirituality, My Name Is Khan.